Difluorocarbene-derived trifluoromethylselenolation of benzyl halides. Issue 10 (14th January 2019) - Chen, Xin-Lei; Zhou, Sheng-Hua; Lin, Jin-Hong; Deng, Qing-Hai; Xiao, Ji-Chang
Abstract : Cu-Promoted difluorocarbene-derived trifluoromethylselenolation of benzyl halides with the Ph3 P + CF2 CO2 − /Se /F − system is described. Abstract : Cu-Promoted difluorocarbene-derived trifluoromethylselenolation of benzyl halides with the Ph3 P + CF2 CO2 − /Se /F − system is described. Three new carbon–heteroatom bonds, a Se–CF2 bond, SeCF2 –F bond, and C–SeCF3 bond, were sequentially formed in the reaction. This work represents the first trifluoromethylselenolation protocol involving an external fluoride for the generation of the key intermediate, CF3 Se − anion.